Latihan batuk efektif terhadap keefektifan jalan napas pada pasien tuberkulosis paru - Hasanuddin, Fitria (Journal of Health Education and Literacy, 2023)
Introduction : Pulmonary tuberculosis is a disease caused by the bacteria Mycobacterium tuberculosis which is also known as acid-fast bacillus (BTA). The entry of tuberculosis bacteria will infect the respiratory tract, reduce the work function of the cilia and will result in the accumulation of secretions in the airways and will cause ineffective airway clearance nursing problems. . Effective cough is a cough method where the client can expend energy and expel phlegm maximally. Objective: To obtain an overview related to the application of effective coughing in pulmonary tuberculosis patients in meeting oxygenation needs. Methods: This study used a quasi-experimental pre and post test design method with data collection methods using observation sheets and interviews. Results: After giving effective coughing exercises, it showed that there was a difference in results from before and after giving effective coughing exercises characterized by reduced coughing, sputum production from 2 cc to 1.1 cc, breath frequency from 28×/mnt to 24×/mnt, No crackles were found, regular breathing rhythm, the type of sputum that changed color, viscosity and the patient was able to produce sputum. Conclusion: There is an effect of giving effective coughing exercises on airway clearance in pulmonary tuberculosis patients. Recommendation: The application of effective coughing exercises can be used as one of the nursing interventions in treating patients with a diagnosis of airway clearance in pulmonary tuberculosis patients who have impaired oxygenation.